Formation of Polymer Films in Organic Photovoltaic Systems - M.N. Orlova; L.I. Kolesnikova; I.V. Schemerov; S.I. Didenko (Журнал нано- та електронної фізики)
Research has indicated that the layer morphology of the films obtained (up to 350 nm thick) gives reason to postulate film structure and composition being dependent on the value of relative fluorescence variation under the influence of a superimposed magnetic field. Moreover, the transmittance and absorption spectra of polymer films which in many ways define the architecture of a photovoltaic cell are highly dependent on the concentration of solutions in the 300-325 nm wavelength range.